Improving early detection of reproductive health through empowering cadres in Kepuharjo village, Cangkringan, Sleman - Sumarni Sumarni; Shinta Prawitasari; Adi Heru Sutomo; ika putri; Santi Yuliani (Journal of Community Empowerment for Health, 2020)
After the catastrophic eruption of Merapi, which was very traumatic, some people had to move to a new neighbourhood which also was a stressor and further might cause mental disorders, especially women's psychiatric disorders. Prolonged stress will suppress the immune system which affects reproductive health, such as menstrual disorders, vaginal discharge, and urinary tract infections. One of the efforts to deal with this problem is to provide assistance related to early detection and overcoming reproductive health disorders for PKK cadres. The purpose of this study was to evaluate the PKK cadre’s skills in early detection and control of reproductive health disorders and to evaluate the decrease of women’s reproductive health disorders in Kepuharjo Village. The target of this study consisted of 40 PKK cadres and 60 women in Kepuharjo Village, Sleman. The early detection module, reproductive health disorder prevention module and early detection skills, reproductive health disorder prevention module, and urine and pap smear laboratory tests were used in the research. The data was presented in quantitative descriptive, using secondary data from community service in June-October 2017. The results of this study were (1) Increasing the average value of early detection skills for reproductive health disorders: stress increased from 39.83 to 57.5; menstrual disorders increased from 29.65 to 57.5; UTI disorders increased from 29.52 to 53.75; vaginal discharge disorders increased from 26.25 to 56.25; breast cancer increased from 16.25 to 51.25. (2) Increasing the average value of reproductive health disorders prevention skills: humour games increased from 41.25 to 82.5 and social support increased from 27.25 to 62.5. (3) Decreased tendency of women’s reproductive health disorders: stress decreased from 39 people (65%) to 21 people (35%); menstrual disorders fell from 51 people (85%) to 31 people (17.67%); UTI disorders decreased from 25 people (41.67%) to 16 people (26.67%); and vaginal discharge decreased from 34 people (56.67%) to 19 people (31.67%). It can be concluded that empowering cadres can improve PKK cadre’s skills in early detection of reproductive health disorders and overcoming reproductive health disorders.